"A View From the Top": Crafting the Male "Domdentity" in Domestic Discipline Relationships. Issue 1 (March 2015) - Carmack, Heather J.; DeGroot, Jocelyn M.; Quinlan, Margaret M.
Domestic discipline (DD) is a relationship approach that advocates wifely submission and male dominance through the use of disciplinary tactics such as spanking. Because DD is seen as a deviant behavioral approach to relationships, men often turn to blogs to chronicle their experiences with DD. These blogs provide insight regarding their identity as a Dominant (Dom), or what they refer to as their "Domdentity." The purpose of our study is to investigate how Doms socially construct and perform their Domdentity. The Domdentity is constructed through a dialectic of discipline and love in the DD relationship, continuously working to maintain the DD relationship, and actively participating, and questioning their roles, in the DD relationship.